Monetary policy efficiency, institutional quality, and financial inclusion in developing countries - Anwar, Cep Jandi; Fitri, Maisya; Suhendra, Indra; Kambara, Roni; Worasutr, Asas (Asian Economic and Financial Review, 2025)
This paper aims to assess how the efficiency of monetary policy and institutional quality affect financial inclusion in 41 developing countries for the period 2010–2023. The study utilizes annual data, employs panel dynamic data analysis, and applies the generalized method of moments (GMM) to ensure the accuracy of the results. This study's findings indicate that monetary policy and institutional quality are essential for the financial sector's integration process. The GMM study indicates that monetary policy efficacy, institutional quality, and central bank interest rates positively influence financial inclusion. Consequently, it is essential to refine monetary policies and develop strong institutions to augment access to financial services. The inverse link between exchange rates, inflation, and financial inclusion indicates that macroeconomic instability significantly endangers financial systems. We identify growth and money supply as the main factors that affect financial inclusion, as they positively impact financial inclusion. These results, therefore, suggest that for countries to enhance financial inclusion, there is a need to ensure stability in the economy as well as an adequate money supply in the system. Our results also contribute to the maintenance of sustainable and balanced economic development as well as equal access to financial resources in developing countries.